THE EFFECTIVENESS OF AI TOOLS IN EVALUATING IDIOMATIC EXPRESSIONS USAGE AMONG LEARNERS - Aamal Aalfaqih (GLOBAL: Education Language and Humanity Journal, 2025)
This paper analyzes the potential of Artificial Intelligence interventions for assessing idiomatic expressions among language learners. Idiomatic expressions are a challenging aspect of language proficiency as their meanings are figurative and culture specific. This paper aspires to explore how current AI technologies like natural language processing, adaptive learning platforms, and automated speech evaluation systems measure learners' understanding of idiomatic expressions. It reviews the strengths and limitations of AI in providing real-time feedback and where AI fails to understand idioms regarding cultural or contextual nuances accurately. It emphasizes the importance of developing more sophisticated AI systems that can consider this cultural understanding. It proposes hybrid models combining AI with human evaluation for fine-grained judgments. Ultimately, it suggests that AI is a promising way of assisting learners in learning an idiomatic language, and future directions are for improving AI's role in idiomatic expression evaluation.